Blockchain‐Empowered H‐CPS Architecture for Smart Agriculture - Xiaoding Wang; Qibin Wu; Haitao Zeng; Xu Yang; Hui Cui; Xun Yi; Md. Jalil Piran; Ming Luo; Youxiong Que (Advanced Science)
Abstract This study integrates blockchain technology into smart agriculture to enhance its productivity and sustainability. By combining blockchain with remote sensing, artificial intelligence (AI), and the Internet of Things (IoT), a Human‐Cyber‐Physical System (H‐CPS) architecture tailored for agricultural applications is proposed. It supports real‐time crop management, data‐driven decision‐making, and transparent trading of agricultural products. A semantic‐based blockchain framework is introduced to address challenges in data management and AI model integration, optimizing production, improving traceability, reducing costs, and enhancing financial security. This framework directly addresses real‐world agricultural challenges, such as optimized irrigation, improved crop breeding efficiency, and enhanced supply chain transparency. These innovations provide practical solutions for modern agriculture, contributing to sustainable development and global food security. Further research and collaboration are encouraged to unlock its full potential in transforming agricultural practices.